2006
DOI: 10.5194/angeo-24-1829-2006
|View full text |Cite
|
Sign up to set email alerts
|

Parallel electric fields inferred during a pulsating aurora

Abstract: Abstract.A sounding rocket, equipped to study pulsating aurora launched from Poker Flat, Alaska on 13 March 1997 at 10:20:31 UT, measured electron precipitation over the range ∼10 eV to 500 keV covering pitch-angles from 0 to 180 • . Data show electrons with energies <1 keV are mostly secondaries produced below the rocket altitude by the higher energy precipitated electrons. We observed nearly equal fluxes of up and down going electrons for energies <1 keV at altitudes from 265 to 380 km. Electron transport si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…For the case of 18 eV, the radar sees . These parameters are well within the ranges known to occur in the auroral ionosphere [21]. The peak value of each spectrum is given at the top right of each panel.…”
supporting
confidence: 67%
“…For the case of 18 eV, the radar sees . These parameters are well within the ranges known to occur in the auroral ionosphere [21]. The peak value of each spectrum is given at the top right of each panel.…”
supporting
confidence: 67%
“…7) taken during the PFISR data interval, and within the field-of-view of the Poker Flat ASC, show this to be a downgoing population and therefore primary precipitation, or perhaps secondary electrons from the conjugate hemisphere (Sato et al, 2002(Sato et al, , 2004 or downward accelerated secondary electrons such as those observed by Williams et al (2006). Fig.…”
Section: Article In Pressmentioning
confidence: 92%
“…It is generally believed that pulsating aurora is caused by energetic electrons (Smith et al, 1980;McEwen et al, 1981) precipitated by pitch-angle diffusion in the vicinity of the equatorial region of the magnetosphere Davidson, 1986a, b;Huang et al, 1990), a result based on velocity dispersion analyzes of sounding rocket observations of energetic electrons in conjunction with pulsating aurora. However, note that a lack of velocity dispersion in the energetic particle measurements has been shown in some instances (Johnstone, 1971;Williams et al, 2006).…”
Section: Introductionmentioning
confidence: 94%
“…Such a complexity is not unexpected. The downgoing low-energy electrons observed by LEO satellites may owe their origin to a number of sources: (a) the low-energy portion of the CPS primary electron precipitation; (b) secondary electrons excited by primary electron precipitation, which subsequently enter the LEO satellite observation as downgoing fluxes via a variety of mechanisms [e.g., Evans, 1974;Evans et al, 1987;Williams et al, 2006]. The secondary electrons can be excited by primary electron precipitation corresponding to pulsating auroras, ambient diffuse auroras, or discrete auroras.…”
Section: On the Low-energy Electron Signature Associated With Papmentioning
confidence: 99%